The Contingent Role of Innovative Leadership in the Digital Era: How Competence Drives Employee Performance While Learning Agility Lags - Afif Fiqhi; Mohammad Mukhsin; Liza Mumtazah Damarwulan (Management Science Research Journal, 2026)
This study examines the influence of work competence and learning agility on employee performance, with innovative leadership as a moderating variable, within the context of digital transformation in the Indonesian agribusiness sector. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 71 employees of PT Agrobisnis Banten Mandiri (Perseroda), a regional-owned enterprise in Banten Province. The findings reveal that work competence significantly and positively affects employee performance (β = 0.582, p < 0.001), confirming its critical role as a foundational capability in the digital era. However, learning agility demonstrates no significant direct effect on performance (β = 0.128, p = 0.453), and innovative leadership neither directly influences performance nor moderates the learning agility–performance relationship. Interestingly, innovative leadership negatively moderates the competence–performance relationship (β = -0.343, p = 0.032), suggesting that excessive emphasis on innovation may dilute the contributions of technical competence in bureaucracy-laden organizations. These findings challenge the universal applicability of learning agility and innovative leadership as performance drivers, contributing to the contingency perspective of human resource management. The study offers practical implications for organizations in transitional economies where bureaucratic structures may constrain the effectiveness of progressive management approaches.